Emerging thin-film nanocomposite (TFN) membranes for reverse osmosis: A review - Zhao, Die Ling; Japip, Susilo; Zhang, Yu; Weber, Martin; Maletzko, Christian; Chung, Tai-Shung (Water research (Oxford), 2020)
Thin-film composite (TFC) membranes are the heart of reverse osmosis (RO) processes for desalination and water reuse. In recent years, nanomaterials with high permeability, selectivity and chemical resistance, and low fouling tendency have begun to emerge and be applied in many other fields. This has stimulated the research on novel RO membranes consisting of nanomaterials (non-porous and porous) in their selective layers. Encouraging results have been demonstrated. Herein, the state-of-the-art developments of polyamide thin-film nanocomposite (TFN) membranes for RO processes are summarized since the concept of TFN was introduced in 2007. While it is obvious that nanomaterials could impart exclusive properties, it should also be noted that significant challenges still exist for research and commercialization of TFN membranes, such as selection of proper nanomaterials, prevention of leaching of nanoparticles, and performance and cost analysis before large-scale RO membrane manufacturing. Future research directions are outlined to offer insights for the fabrication of much advanced TFN membranes with optimal interface morphology and separation performance. [Display omitted] •Performances of thin-film nanocomposite (TFN) reverse osmosis (RO) membranes are summarized.•Different methods to incorporate different nanomaterials into the selective layers are introduced.•The challenges and future of TFN RO membranes are elaborated.